Biomechanical evaluation of two internal fixation systems for the treatment of mandibular symphyseal fracture. (May 2023) - Wongwaithongdee, Udom; Inglam, Samroeng; Chantarapanich, Nattapon
Graphical abstract Due to the disadvantage of maxillomandibular fixation, the semi-rigid and rigid internal fixations have been employed to provide early mouth motion. To find the proper fixation and adequate stability, the biomechanical performance of these systems was assessed using Finite Element (FE) method. The 3D mandible model with a symphyseal fracture, teeth, periodontal ligament, and fixation devices were created for the FE analyzes. The bone structure was determined as a transverse isotropic whereas the fixation devices were titanium. The load includes Masseter, Medial Pterygoid, and Temporalis muscular forces as well as the occlusal forces acting on first molars, canines, and incisors. The maximum stress occurs at the center of fixation devices at symphyseal fracture. The maximum stress values were 877.4 MPa for the reconstruction plate and 646.8 MPa for the mini-plates. The plates maintained the fracture width at mid-region better than superior and inferior. The maximum fracture gap were 1.10 and 0.78 mm for reconstruction plate and mini-plates, respectively. The fracture site's elastic strain stabilized with the reconstruction plate was 1089.0 microstrains and with the mini-plates was 399.6 microstrains. The treatment of a mandibular symphyseal fracture using a mini-plates provides more adequate fracture stability for new bone formation and mechanically safer than locking reconstruction plate. Mini-plates fixation was able to control the fracture gap better than the reconstruction plate. Mini-plates technique was considered as the first choice of internal fixation, however, a reconstruction plate can also be used in case of unavailability and complication related to mini-plating.